Contemporary Progresses in Ultrasonic Welding of Aluminum Metal Matrix Composites - Selvaraj, Senthil Kumaran; Srinivasan, Kathiravan; Chadha, Utkarsh; Mishra, Rajat; Arpit, Kurane; Apurb, Kumar; Hu, Yuh-Chung (Frontiers in Materials, 2021)
The Aluminum metal matrix with particulate reinforcements is the new future of the coming industrial revolution due to the higher strength and also due to its availability. The composite reinforcements like SiC, TiB2, B4C, etc., are the major contributor to the increased strength of the Aluminum metal matrix, which can be an optimal choice, also with lower costs other than those scarce/rare metals with high strength with low life in some applications where Aluminum is into consideration or proven to withstand. Ultrasonic welding is the process, where, we get the electrical energy, which is converts and amplifies into vibration energy for the welding to occur. The challenge we face today is the thickness limitations in ultrasonic welding. The ultrasonic welding of the Aluminum metal sheet with the reinforcements may affect it, as the addition of particulate reinforcements will increase the strength of the Aluminum matrix. The ultrasonic welding only supports a metal sheet with thickness up to 2.5 mm in the case of an Aluminum plain sheet, and if the strength increases in the same Aluminum metal matrix, then the next step to proceed with it to achieve ultrasonic welding with the same thickness of Aluminum matrix along with the reinforced composites, which has more strength than that of a standard Aluminum sheet. This review will focus on the parameters and the factors which may help decrease the difficulties of Ultrasonic Welding of Aluminum MMC, alongside reviewing the current technologies and research works.